Copper-iron metabolism interaction in rats - Ramírez-Cárdenas, Lucía; Costa, Neuza Maria Brunoro; Reis, Fernando Pinheiro (Nutrition research (New York, N.Y.), 2005)
Iron deficiency anemia can be due to copper deficiency, even when iron intake is adequate. The objective of this study was to evaluate the interaction of copper with iron metabolism in anemic rats, using standard (copper and iron sulfate) or rice and beans diets containing the same iron concentration (24 ppm) but different levels of copper (2, 4, 6, or 12 ppm). A factorial model (2 × 4) was used together with a control treatment (0 ppm Cu, 24 ppm Fe), and the 9 treatments were randomly assigned to 8 blocks. The copper-iron interaction was evaluated by regression analysis. An increase in the levels of hemoglobin, hematocrit, and serum iron was observed with increased copper concentration, reaching a maximum value of about 6 ppm. Low hematological levels were probably due to deficiency of ceruloplasmin and cytochrome c oxidase, which are copper-dependent enzymes required for iron metabolism. Both copper deficiency and excess result in anemia. However, an excess of up to 12 ppm was less harmful than the absence of copper in the diet. As copper concentration in the control diet increases, nonenzymatic hemoglobin glycosylation decreases to about 6 ppm. An opposite effect is observed as copper concentration increases in the diet. A significant difference ( P < .05) between the two diets was observed in the hemoglobin and glycosylated hemoglobin levels. This suggests lower bioavailability of these minerals in a rice and beans diet.